KWT Resilience in Dealing with Climate Disasters Through Agricultural Innovation: A Case Study of KWT Bougenville Assisted by PT Pertamina Patra Niaga AFT Babullah - Sinki Anggriani; Fiki Nafila; Suhada Widi Prastyo (Jurnal Indonesia Sosial Teknologi, 2025)
Women Farmers Groups (KWT) play an important role in maintaining local food security, especially amidst the increasing threat of climate disasters. Climate change causes various problems such as decreased agricultural land productivity, drought, flooding, and weather uncertainty. This encourages the need for agricultural innovations that can increase the resilience of farmer groups, including KWT Bougenville which is under the guidance of PT Pertamina Patra Niaga AFT Babullah. This study aims to understand how KWT Bougenville deals with the impacts of climate change through the application of appropriate and sustainable agricultural innovations. This study uses a qualitative research method. The data collection technique in this study is through literature studies. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The results of the study show that KWT Bougenville has succeeded in increasing resilience in dealing with climate disasters through various agricultural innovations, such as the use of efficient irrigation technology, the application of more adaptive planting patterns, and sustainable land management. The guidance of PT Pertamina Patra Niaga AFT Babullah also plays a significant role in providing support, both in terms of training and technological assistance. However, there are still challenges in terms of resources and technological limitations that need to be overcome to achieve more optimal resilience.  These findings are not only relevant for direct stakeholders, but also contribute to the development of sustainable agriculture at the national level.